Role Of Receiving Section In Assuring Quality Of Ordered Goods In Tentrem Hotel Semarang During Covid-19 Pandemic - Oei Tania Sabella; Izza Ulumuddin Ahmad Asshofi (FKIP, Universitas Palangka Raya, 2023)
This project was made considering the importance of the quality of an item and the importance of the role of the part in charge of carrying out the receiving of the hotel ordered goods. This final project aims to explain the role of the receiving section in ensuring that the quality of hotel orders during the pandemic remains good and according to applicable standards. The research method used is qualitative method and literature study and the data collection method used in this project uses the method of observation, interviews and documentation so that the data obtained is more accurate. The results of this study show the importance of the role of the receiving section in ensuring the quality of hotel ordered goods, especially during the COVID- 19 pandemic, this final project underscores the importance of the role of the receiving section in maintaining the quality of goods. Hotel orders during the waiting time until then received by the user who has ordered the item especially during COVID-19 pandemic through various means such as monitoring, health protocol discipline and receiving staff’s efficiency.